Najnowsze odkrycia kafli z zamku w Chudowie koło Gliwic - Tarasiński, Arkadiusz (Acta Universitatis Lodziensis. Folia Archaeologica, 2010)
Chudów is situated in Silesian voivodship, in Gliwice district (fig. l). The castle was built by Jan Gierałtowski in the 1st half of the 16th century (fig. 2). The latest archaeological excavations confirmed also traces of earlier occupation (wooden), dated to the Middle Ages. The end of the castle functioning falls to the 2nd half of the 19th century. Archaeological research conducted since 2001 yielded many artifacts, among which there were over 15.500 tile fragments. This number includes nearly 5.050 fragments coming from face parts, other fragments are parts of flanges or unidentified. Among all the tiles, over 180 different ornamental motifs were distinguished.